2016
DOI: 10.1186/s13023-016-0488-x
|View full text |Cite
|
Sign up to set email alerts
|

Altered skeletal muscle (mitochondrial) properties in patients with mitochondrial DNA single deletion myopathy

Abstract: BackgroundMitochondrial myopathy severely affects skeletal muscle structure and function resulting in defective oxidative phosphorylation. However, the major pathomechanisms and therewith effective treatment approaches remain elusive. Therefore, the aim of the present study was to investigate disease-related impairments in skeletal muscle properties in patients with mitochondrial myopathy. Accordingly, skeletal muscle biopsies were obtained from six patients with moleculargenetically diagnosed mitochondrial my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 53 publications
(79 reference statements)
0
11
1
1
Order By: Relevance
“…Studies on the metabolic profile of muscle fibers in patients with OXPHOS deficiency are sparse and sometimes contradictory, reporting either no fiber type predominance,21 a type I predominance,15, 43, 44, 45, 46 or a type II predominance 47. Interestingly, we found higher respiratory chain deficiency in type II fibers over type I in 5 of 6 patients.…”
Section: Discussioncontrasting
confidence: 47%
“…Studies on the metabolic profile of muscle fibers in patients with OXPHOS deficiency are sparse and sometimes contradictory, reporting either no fiber type predominance,21 a type I predominance,15, 43, 44, 45, 46 or a type II predominance 47. Interestingly, we found higher respiratory chain deficiency in type II fibers over type I in 5 of 6 patients.…”
Section: Discussioncontrasting
confidence: 47%
“…Alterations in the mitochondrial genome change the morphology and physiology of specific tissues. In skeletal muscle, Gehrig et al () observed a fiber‐type switching from type I and more oxidative muscle fibers towards type II and more glycolytic muscle fibers in humans with mitochondrial myopathy. This type of mitochondrial defect changes the form and function of skeletal muscle leading to variations in the predominant energy sources used, increased muscle weakness, and decreased muscle health by a loss of oxidative capacity.…”
Section: Mitochondriamentioning
confidence: 99%
“…Adicionalmente, los pacientes pueden presentar dificultades en el control de las infecciones (14) . La CPEO se manifiesta con síntomas leves en la niñez, tal como ocurrió en el paciente que reportamos (16). La debilidad muscular ocular se desarrolla gradualmente durante años e incluso décadas.…”
Section: Discussionunclassified